The Effect of Aerobic Exercise on Lowering the Pulse Rate of Isitirahat in Women Over 40 Years of Age Who Work Indoors - Regina Safira Patricia; Prima Arundani; Dody Taruna; Asami Rietta Kumala (Journal of Social Research, 2026)
This study aims to determine the effect of aerobic exercise on reducing resting heart rate in women over 40 years old who work indoors. This research employed an experimental quantitative design with a one-group pre-test–post-test approach. The sample consisted of 30 women aged over 40 years who worked indoors and met the inclusion criteria. The intervention involved low-impact aerobic exercise performed for four weeks, three times per week, for 30 minutes per session. Resting heart rate was measured before and after the intervention. Data were analyzed using the paired sample t-test after fulfilling the Shapiro–Wilk normality test. The results showed that the average resting heart rate before aerobic exercise was 80.50 bpm and decreased to 73.07 bpm after the intervention. The reduction of 7.43 bpm was statistically significant (p = 0.000), indicating cardiovascular adaptations such as increased parasympathetic activity and improved cardiac efficiency. Aerobic exercise has a significant effect on reducing resting heart rate in women over 40 years old who work indoors. Regular aerobic exercise for four weeks is effective in improving cardiac efficiency and cardiovascular fitness.